2019
DOI: 10.1016/j.jcis.2019.07.080
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hydrophobicity and durability of functionalized aluminium oxide nanoparticle coatings with magnetite nanoparticles–links between morphology and wettability

Abstract: Comparison of hydrophobicity and durability of functionalized aluminium oxide nanoparticle coatings with magnetite nanoparticles-links between morphology and wettability,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 35 publications
(70 reference statements)
3
15
0
Order By: Relevance
“…However, with further increase of the wt. (%) NPs, the wettability decreases and the EPNCs become hydrophobic, which is in accordance with the observation of Hill et al in 2019 [21]. From Figure 3, the major increase of about 53% compared with CS was observed for 3 wt.…”
Section: Contact Anglesupporting
confidence: 90%
See 3 more Smart Citations
“…However, with further increase of the wt. (%) NPs, the wettability decreases and the EPNCs become hydrophobic, which is in accordance with the observation of Hill et al in 2019 [21]. From Figure 3, the major increase of about 53% compared with CS was observed for 3 wt.…”
Section: Contact Anglesupporting
confidence: 90%
“…In recent years, special attention has been paid to EPs filled with NPs. These nanofillers (e.g., silicon dioxide (SiO2) [12][13][14], titanium dioxide (TiO2) [15,16], aluminum oxide (Al2O3) [17][18][19]) are characterized by their specific shape and size (nanoscale), high surface areas, surface pretreatment, and the degree of dispersion into the EP matrix [1,2,4,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consideration of the dynamic wetting and sliding angle data for the embedded nanoparticle film suggests that this surface exhibits petal-like wetting behaviour where the high adhesion is caused by water penetrating into grooves formed between the microstructures 34 . AFM imaging showed that the embedded nanoparticles displayed a root mean squared roughness similar to when the particles are deposited onto the plastic at room temperature 36 (222 nm versus 210 nm), which suggests that topographic variations that could affect this behaviour do not exist on the nanoscale. The AFM image of the embedded particles from which this measurement was performed is displayed in Fig.…”
Section: Wetting Behaviourmentioning
confidence: 96%